Impacts of single nucleotide polymorphisms in Fc gamma receptor IIA (rs1801274) on lung transplant outcomes among Japanese lung transplant recipients. (19th September 2021) - Kayawake, Hidenao; Chen‐Yoshikawa, Toyofumi F.; Tanaka, Satona; Tanaka, Yuka; Ohdan, Hideki; Yutaka, Yojiro; Yamada, Yoshito; Ohsumi, Akihiro; Nakajima, Daisuke; Hamaji, Masatsugu; Egawa, Hiroto; Date, Hiroshi
Summary: This study aimed to analyze the influences of single nucleotide polymorphisms (SNPs) in Fc gamma receptor IIA (FCGR2A) on postoperative outcomes after lung transplantation (LTx). We enrolled 191 lung transplant recipients [80 undergoing living‐donor lobar lung transplants (LDLLTs) and 111 undergoing deceased‐donor lung transplants (DDLTs)] in this study. We identified SNPs in FCGR2A (131 histidine [H] or arginine [R]; rs1801274) and reviewed the infectious complication‐free survival after ICU discharge. The SNPs in FCGR2A comprised H/H ( n  = 53), H/R ( n  = 24), and R/R ( n  = 3) in LDLLT and H/H ( n  = 67), H/R ( n  = 42), and R/R ( n  = 2) in DDLT. Recipients with H/H (H/H group) and those with H/R or R/R (R group) were compared in the analyses of infectious complications. In multivariate analyses, the R group of SNPs in FCGR2A was associated with pneumonia‐free survival {HR: 2.52 [95% confidence interval (CI): 1.35–4.71], P  = 0.004}, fungal infection‐free survival [HR: 2.50 (95% CI: 1.07–5.84), P  = 0.035], and cytomegalovirus infection‐free survival [HR: 2.24 (95% CI: 1.07–4.69), P  = 0.032] in LDLLT, but it was not associated with infectious complication‐free survival in DDLT. Therefore, in LDLLT, more attention to infectious complications might need to be paid for LTx recipients with H/R or R/R than for those with H/H. Abstract : Although there were no significant differences in prognoses after LTx among SNPs in FCGR2A, a SNP in FCGR2A (H/R or R/R) was detected as a significant predictive factor for pneumonia, fungal infection, and CMV infection after ICU discharge among LDLLT recipients.